A study on non-cycloplegic and cycloplegic streak retinoscopy and autorefractometry in children - Kedia, Puja; Baruah, Mamoni (International Journal of Research in Medical Sciences, 2022)
Background: Refractive errors in children should be identified and corrected as early as possible to prevent irreversible vision loss. Therefore, accurate methods of objective refraction should be employed by paediatric eye care providers when examining young children. The purpose of this study was to assess the accuracy of non-cycloplegic and cycloplegic retinoscopy and autorefractometry as objective methods of refraction, and to determine their suitability with subjective acceptance. Methods: The one-year study included 453 children of 3-15 years. Noncycloplegic autorefraction and streak retinoscopy were done. These were followed by cycloplegic autorefraction and streak retinoscopy. Cycloplegia was attained by using atropine sulphate 1% eye drops and cyclopentolate hydrochloride 1% eyedrops for children of 3-7 years and 8-15 years respectively. Postmydriatic subjective refraction was then done. Results were compared using Analysis of Variance (ANOVA). Calculated p<0.05 was considered as statistically significant. Results: Noncycloplegic methods showed underestimation of hypermetropia and overestimation of myopia. The spherical and cylindrical measurements of cycloplegic autorefraction were equivalent to cycloplegic retinoscopy. Axis of cycloplegic autorefraction was better than cycloplegic retinoscopy. Conclusions: The most accurate method of objective refraction is cycloplegic retinoscopy. However, the spherical and cylindrical measurements of cycloplegic autorefraction can be substituted for conventional cycloplegic retinoscopy in young children.